Diagnostic Errors in Interactive Telepathology - G. Stauch; K. W. Schweppe; K. Kayser (Analytical Cellular Pathology)
Telepathology (TP) as a service in pathology at a distance is now widely used. It is integrated in the daily workflow of numerous pathologists. Meanwhile, in Germany 15 departments of pathology are using the telepathology technique for frozen section service; however, a common recognised quality standard in diagnostic accuracy is still missing. In a first step, the working group Aurich uses a TP system for frozen section service in order to analyse the frequency and sources of errors in TP frozen section diagnoses for evaluating the quality of frozen section slides, the important components of image quality and their influences an diagnostic accuracy. The authors point to the necessity of an optimal training program for all participants in this service in order to reduce the risk of diagnostic errors. In addition, there is need for optimal cooperation of all partners involved in TP service.